Peningkatan Hasil Belajar Matematika Materi Trigonometri melalui Penerapan Model Pembelajaran Problem Based Learning pada Siswa Kelas X SMA Negeri 1 Gomo Tahun Pelajaran 2022/2023 - Febriani Halawa (Departement of Mathematics Education, 2024)
This thesis is motivated by problems that arise in a class in the mathematics subject Trigonometry, namely low learning outcomes because students do not like the teacher's way of teaching. So teachers need to apply a learning model or method as proposed by the author, namely the Problem Based Learning model. This research is intended to answer the problem: Can the Problem Based Learning model improve the mathematics learning outcomes of trigonometry material in class X students at SMA Negeri 1 Gomo for the 2022/2023 academic year. This problem was discussed through classroom action research which was carried out in 2 (two) cycles with each cycle consisting of 4 components or stages, namely: planning, implementation (action), observation, and evaluation (reflection). Data collection in this research used observation and tests. This research concludes that the application of the Problem Based Learning model can improve the mathematics learning outcomes of trigonometry material in class X students at SMA Negeri 1 Gomo for the 2022/2023 academic year. results of learning mathematics trigonometry material. The increase in students who completed their studies can be seen from the first cycle of students who completed 13 students or 40.62% and those who did not complete 19 students or 59.38%. Meanwhile, in cycle II, there were 28 students who completed it or 87.5% and 4 students who did not complete it or 12.5%. The criteria for classical completeness ≥ 85% were achieved in cycle II with a percentage of 87.5%. Then the cycle is stopped and declared successful.